2013
DOI: 10.1371/journal.pone.0072963
|View full text |Cite|
|
Sign up to set email alerts
|

Normal Mutation Rate Variants Arise in a Mutator (Mut S) Escherichia coli Population

Abstract: The rate at which mutations are generated is central to the pace of evolution. Although this rate is remarkably similar amongst all cellular organisms, bacterial strains with mutation rates 100 fold greater than the modal rates of their species are commonly isolated from natural sources and emerge in experimental populations. Theoretical studies postulate and empirical studies teort the hypotheses that these “mutator” strains evolved in response to selection for elevated rates of generation of inherited variat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0
2

Year Published

2014
2014
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 70 publications
(81 reference statements)
0
36
0
2
Order By: Relevance
“…Recent findings have suggested that mutators may tend to attenuate their increased mutation rate over time [16],[54],[55], perhaps to avoid the harmful effects of Muller's Ratchet. Thus both tradeoffs in alternative environments and mutation load in selective environments may contribute to the paradox that over the short term lineages often benefit from elevated mutation rates, but the long-term trend across phylogenies has been for stability in mutation rates of free-living microbes [56].…”
Section: Discussionmentioning
confidence: 99%
“…Recent findings have suggested that mutators may tend to attenuate their increased mutation rate over time [16],[54],[55], perhaps to avoid the harmful effects of Muller's Ratchet. Thus both tradeoffs in alternative environments and mutation load in selective environments may contribute to the paradox that over the short term lineages often benefit from elevated mutation rates, but the long-term trend across phylogenies has been for stability in mutation rates of free-living microbes [56].…”
Section: Discussionmentioning
confidence: 99%
“…Tröbner and Piechocki were unable to characterize either the genetic basis or the population dynamics of the modifier(s) responsible for decreasing the mutation rate but showed that the mutT allele itself had not changed. Clones with lower mutation rates have also been isolated from mutS mutator populations of E. coli after experimental colonization of the mouse gut (Giraud et al, 2001) and in vitro propagation by serial passaging (Turrientes et al, 2013). Another recent example of such short-term selection against strong mutator phenotypes is provided by the work of Loh et al (2010), who co-propagated 66 E. coli strains with different mutation rates for 350 generations: moderate-strength mutators were most favored in all of their experimental populations.…”
Section: Why Aren't All Asexually Reproducing Populations Fixed For Mmentioning
confidence: 99%
“…A recent study in Pseudomonas aeruginosa also showed that a mutS mutator allele can provide inherent resistance to oxidative stress and so could have a direct fitness benefit in certain environments (Torres- Barceló et al, 2013). On the other hand, a different study in mutS E. coli populations has documented the appearance of apparently directly beneficial variants with lower mutation rates (Turrientes et al, 2013). In general, it is conceivable that mutation rate modifiers can have pleiotropic effects on fitness that affect their propensity to spread in natural populations, but at present it is unclear whether such effects would contribute to stabilizing the mutation rate at the low wild-type levels that prevail in most natural populations.…”
Section: Why Aren't All Asexually Reproducing Populations Fixed For Mmentioning
confidence: 99%
“…2012; Turrientes et al. 2013; Wielgoss et al. 2013), the mutation rate of an adapted population carrying a mutator allele has been seen to decrease and the time to fixation has been measured, but a theoretical understanding of this time scale is missing.…”
Section: Introductionmentioning
confidence: 99%